Modifying Lipid Rafts Promotes Regeneration and Functional Recovery - Nardos G. Tassew; Andrea J. Mothe; Alireza P. Shabanzadeh; Paromita Banerjee; Paulo D. Koeberle; Rod Bremner; Charles H. Tator; Philippe P. Monnier (2014)
Ideal strategies to ameliorate CNS damage should promote both neuronal survival and axon regeneration. The receptor Neogenin promotes neuronal apoptosis. Its ligand prevents death, but the resulting repulsive guidance molecule a (RGMa)-Neogenin interaction also inhibits axonal growth, countering any prosurvival benefits. Here, we explore strategies to inhibit Neogenin, thus simultaneously enhancing survival and regeneration. We show that bone morphogenetic protein (BMP) and RGMa-dependent recruitment of Neogenin into lipid rafts requires an interaction between RGMa and Neogenin subdomains. RGMa or Neogenin peptides that prevent this interaction, BMP inhibition by Noggin, or reduction of membrane cholesterol all block Neogenin raft localization, promote axon outgrowth, and prevent neuronal apoptosis. Blocking Neogenin raft association influences axonal pathfinding, enhances survival in the developing CNS, and promotes survival and regeneration in the injured adult optic nerve and spinal cord. Moreover, lowering cholesterol disrupts rafts and restores locomotor function after spinal cord injury. These data reveal a unified strategy to promote both survival and regeneration in the CNS.